2014
DOI: 10.1681/asn.2013060604
|View full text |Cite
|
Sign up to set email alerts
|

CKD and the Risk of Incident Cancer

Abstract: Previous studies report a higher risk of cancer in patients with ESRD, but the impact of less severe CKD on risk of cancer is uncertain. Our objective was to evaluate the association between level of kidney function and subsequent cancer risk. We performed a retrospective cohort study of 1,190,538 adults who were receiving care within a health care delivery system, had a measurement of kidney function obtained between 2000 and 2008, and had no prior cancer. We examined the association between level of eGFR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
192
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(209 citation statements)
references
References 44 publications
12
192
4
1
Order By: Relevance
“…Lowrance et al 7 sought to account for bias resulting from reverse causation by restricting their analysis to individuals without a history of dialysis or renal transplantation before study entry, by excluding incident cancers diagnosed during the first 2 years of follow-up, and by excluding serum creatinine measurements obtained ,3 months before an incident cancer diagnosis. Although these exclusion criteria should provide some reassurance that the observed association reflects an etiologic role of CKD in renal carcinogenesis, future studies characterizing kidney function earlier in time before RCC diagnosis would further strengthen the argument against reverse causation bias.…”
mentioning
confidence: 99%
“…Lowrance et al 7 sought to account for bias resulting from reverse causation by restricting their analysis to individuals without a history of dialysis or renal transplantation before study entry, by excluding incident cancers diagnosed during the first 2 years of follow-up, and by excluding serum creatinine measurements obtained ,3 months before an incident cancer diagnosis. Although these exclusion criteria should provide some reassurance that the observed association reflects an etiologic role of CKD in renal carcinogenesis, future studies characterizing kidney function earlier in time before RCC diagnosis would further strengthen the argument against reverse causation bias.…”
mentioning
confidence: 99%
“…51 For example, the increased risk for RCC was 100-fold for patients with ESRD, 51 and it was increased for patients with CKD (stage 3/4) as well. 52 The incidence of renal cancers rose incrementally with higher CKD stages, and the strongest association was with ccRCC. 52 Remarkably, the incidence of renal cancers also varied according to periods of renal function (transplant) versus nonfunction (graft failure requiring dialysis) among 202,195 renal transplant candidates.…”
Section: Ckd Prevalence and Risk Of Rccmentioning
confidence: 97%
“…52 The incidence of renal cancers rose incrementally with higher CKD stages, and the strongest association was with ccRCC. 52 Remarkably, the incidence of renal cancers also varied according to periods of renal function (transplant) versus nonfunction (graft failure requiring dialysis) among 202,195 renal transplant candidates. 53 Incident rates of renal cancer rose when renal function was lost and fell after transplantation, and this pattern recurred during subsequent transplantations.…”
Section: Ckd Prevalence and Risk Of Rccmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Lowrance et al [32] found a positive association between demonstrated that chronic kidney disease increased the risk of kidney cancer in the American population while Lai et al [29] found a positive association between chronic kidney disease and the risk of kidney cancer in the Taiwanese population.…”
Section: Risk Factors Medical Conditionsmentioning
confidence: 99%